Sosialisasi dan Pelatihan Terkait Media Daring Google Classroom dan Google Form di Masa Pandemi Covid 19 pada Sekolah Dasar Negeri 23 Palembang - Muhammad Ichsan Siregar; Nur Khamisah; Sri Maryati; Trie Sartika Pratiwi; Lina Dameria Siregar; Hera Febria Mavilinda; Yusnaini Yusnaini; Nilam Kesuma (Penerbit Goodwood, 2021)
Purpose: This service aims to socialize and offer training related to the use of online study rooms through Google Classroom And Google Form to teachers and employees at State Elementary School 23 Palembang. Method: The method used when carrying out this service activity is the lecture method and direct practice. Both provide material introduction to theory and direct practice of using Google Classroom and Google Form for both teachers and employees. Results: From this service activity in the form of providing material and direct practice, both teachers and employees who tried Google Classroom and Google Form got good results. Teachers and employees understand the use of online media in the form of Google Classroom And Google Form. Conclusions: After getting materials and practices for using online media, Google Classroom and Google Form, teachers and employees are accustomed to use these online media throughout the COVID-19 pandemic.